Experimental and computational characterization of carbon fibre based structural battery electrode laminae - David Carlstedt and Florian Rittweger and Kennth Runesson and Adriana M. Navarro-Suárez and Johanna Xu and Shanghong Duan and Fredrik Larsson and Karl-Ragmar Riemschneider and Leif E. Asp (Composites science and technology, 2022)
In this paper, electrode laminae consisting of carbon fibres embedded in structural battery electrolyte are characterized with respect to their multifunctional (i.e. combined electrochemical and mechanical) performance utilizing experimental and numerical techniques. The Effects of electrode lamina thickness on electrochemical performance are measured. Li-insertion induced longitudinal expansion of carbon fibre electrodes is measured in situ during electrochemical cycling. A previously developed coupled electro-chemo-mechanical finite element model is validated based on experimental data. We expect that the utilized computational framework and experimental data open a route to develop high-performing, both mechanically and electrochemically, carbon fibre based battery electrode laminae for future lightweight structural components with energy storage ability.
Keywords: Carbon fibres; Multifunctional composites; Electro-chemical behaviour; Electro-mechanical behaviour; Biomimetics